Growth, enzymatic glutathione peroxidase activity and biochemical status of juvenile barramundi (Lates calcarifer) fed dietary fermented soybean meal and organic selenium - Ilham, I.; Fotedar, Ravi (Springer Netherlands, 2017)
Solvent-extracted soybean meal (SBM) was fermented using baker’s yeast Saccharomyces cerevisae at 30 °C for 5 days. Four isonitrogenous and isocaloric diets containing 75% SBM protein, either fermented or non-fermented (SBMand FSBM), and supplemented or not with organic Se (OS) (SBMOS and FSBMOS), were fed to triplicate groups of juvenile barramundi (Lates calcarifer) (initial weight of 5 g) for 75 days. A fishmeal (FM)-based diet formulated for juvenile barramundi was used as a reference diet. The growth of fish was significantly affected by either the interaction of SBM type or by the OS level. In fish fed diets supplemented with OS (SBMOS and FSBMOS), final weight (FW), specific growth rate (SGR) and weight gain (WG) were higher in fish fed the fermented SBM(FSBMOS) than in those fed the non-fermented SBM(SBMOS). The apparent digestibility coefficient (ADC) of protein was higher in the fish fed the fermented SBM, either supplemented or unsupplemented with OS. However, there were no significant differences in the ADC of dry matter (DM) and lipids among the tested diets and in comparison to the reference diet. The haematocrit and leucocrit of fish fed the FSBMOS diet were lower than those of fish fed the FM diet. Furthermore, glutathione peroxidase (GPx) activity was significantly influenced by OS supplementation in the experimental diets; GPx activity was greater in the fish fed diets supplemented with OS. Creatinine kinase (CK) of all groups of fish was higher than the CK of those fed the reference diet. These results suggest that with a proper nutritional level, OS supplementation may act as an important factor in enzymatic GPx activity and in the haematology and blood biochemistry status of juvenile barramundi fed fermented SBM-based diets, encouraging improvement of the overall growth performance.